Answer:
the answer is c, less than or equal to 4
Answer:
y = -3.3 then -7.1
y = -7.1 then -10.9
y = -2.6 then -6.4
y = 1 then -2.8
y = 4.2 then 0.4
Step-by-step explanation:
(-3.8)+0+y can be simplified to -3.8 + y. Evaluate each value for y by substituting it into the expression and solving.
y = -3.3 then -3.8 + -3.3 = -7.1
y = -7.1 then -3.8 + -7.1 = -10.9
y = -2.6 then -3.8 + -2.6 = -6.4
y = 1 then -3.8 + 1 = -2.8
y = 4.2 then -3.8 + 4.2 = 0.4
Answer:
(x^2 + x -1) x (x^2+3x-3)
Step-by-step explanation:
-6x-5+x^4+4x^3-x^2+8
-6x+3+x^4+4x^3-x^2
-6x+3+x^4+x^3+3x^3-x^2
-3x-3x+3+x^2 x(x^2+x-1)+3x^3 +3x^2-3x^2
3x *(x^2+x+x-2)-3(x^2+x-1)+x^2 *(x^2+x-1)
= (x^2+x-1) x (x^2+3x-3)
* means multiply btw
The answer would be b.100 because its clearly not a right triangle
Answer:
the negative and positive number line???? what exactly are you asking
Step-by-step explanation: